Impact implementation of law number 11 in 2012 concerning children's justice system for development of children - Sri Haryaningsih; Titik Hariyati (Indonesian Institute for Counseling, Education and Theraphy (IICET), 2021)
Law number 11 of 2012 concerning the Child Criminal Justice System (UU SPPA) which has been published has brought a change in the paradigm of child crime with a prison nuance to a more child-friendly concept towards restorative justice. However, the phenomenon found in minors is still undergoing legal proceedings. Meanwhile, during the legal process, children are detained in detention centers and placed outside the Special Development Institution for Children (LPKA) and Temporary Child Placement Agency (LPAS). This research was conducted using a qualitative method to child prisoners in West Kalimantan Province. This research was conducted by conducting structured interviews and it carried the analysis of this research out with three lines, namely data reduction, data presentation and conclusion/verification. The findings of the study were helping to children in legal conflict in a fairly good range, even though help from expert advocates and the community had not been fully achieved. The reason it still places many children outside the LPKA is because there are no LPKA or LPAS in the district. Therefore, it is necessary to add LPKA or LPAS to pay attention to the needs of education, health and the needs of children of inmates so that it guarantees their growth and development.